Investigation of Constipation Frequency and Development Risk in Cancer Patients - Nazlı Öztürk; Burcu Çelik Kocabıyık; Fatma Arıkan; Hasan Şenol Coşkun (Dokuz Eylul University, 2020)
Background: Constipation is one of the common symptoms in cancer patients, and many factors such as lack of mobility, insufficient fluid intake, chemotherapy, radiotherapy and opioid use can be effective in this symptom. Close monitoring of cancer patients in terms of the risk of developing constipation contributes to the early diagnosis of this symptom. Objectives: The aim of this study is to determine the frequency / risk of development and some factors affecting the development of constipation in cancer patients hospitalized in the oncology clinic. Methods: This descriptive study in October 2018-February 2019, between the age of 18, was conducted with 129 patients who were diagnosed with cancer. The data were collected using 'Individual Identification Form' and 'Constipation Risk Assessment Scale'. The evaluation of the data was done by Chi-square, Mann-Whitney U test. Results: The mean age of the patients is 59 ± 1.12 years, 34.2% are women, 65.8% are men and frequency of constipation is 62%. It has been determined that there is a statistically significant difference between the patients being construed and continuous opioid treatment, the reason for hospitalization and the presence of metastasis. Constipation rate was higher in patients who were constantly receiving opioid therapy and hospitalized for supportive treatment (p < .05). It was found that the risk of developing constipation was moderate level (13.1 ± 4.3) in patients who were not constipated. Conclusion: In our study, it was determined that the majority of patients hospitalized in the oncology clinic experienced constipation, continuous opioid treatment, supportive treatment and the presence of metastasis were effective in patients' constipation and cancer patients who were not constipated were at moderate risk.